Urolithin A Inhibits the Catabolic Effect of TNFα on Nucleus Pulposus Cell and Alleviates Intervertebral Disc Degeneration in vivo - Liu, Huiyong; Kang, Honglei; Song, Chao; Lei, Zuowei; Li, Li; Guo, Jianfeng; Xu, Yong; Guan, Hanfeng; Fang, Zhong; Li, Feng (Frontiers in Pharmacology, 2018)
Low back pain is a common worldwide disease that causes an enormous social economic burden. Intervertebral disc degeneration (IDD) is considered as a major cause of low back pain. The process of IDD is complicated and involves both inflammation and senescence. The production of pro-inflammatory cytokines, including tumor necrosis factor (TNF)α and interleukin (IL)-1β, is increased in the degenerating intervertebral disc, inducing extracellular matrix degradation. Urolithin A (UA) is a metabolite compound resulting from the degradation of ellagitannins by gut bacteria. UA has been reported to be useful for the treatment of diseases associated with inflammation, senescence and oxidative damage. Therefore, we hypothesized that UA may be an effective treatment for IDD. This study examined the effects of UA on IDD in vitro and in vivo and explored their underlying mechanisms. Our findings indicated that UA could attenuate cellular senescence induced by hydrogen peroxide in nucleus pulposus cells. UA treatment decreased TNFα-induced matrix metalloproteinase production and the loss of collagen II. At the molecular level, UA considerably blocked the phosphorylation of the extracellular signal-regulated kinase, c-JUN N-terminal kinase and Akt pathways. In vivo study illustrated that UA treatment could ameliorate IDD in a needle-punctured rat tail model, which was evaluated by X-ray imaging, magnetic resonance imaging and histological analysis. Thus, the results of our study revealed that UA may be a useful therapeutic agent for the treatment of IDD.